2014
DOI: 10.1111/tbj.12254
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated Radiation Therapy for Early Stage Breast Cancer: Outcomes, Toxicities, and Cost Analysis

Abstract: A French prospective randomized trial comparing whole breast radiotherapy with 45 Gy in 25 fractions versus 23 Gy in four fractions demonstrated equivalent 5-year local control and survival. On the basis of this data, we offer the hypofractionated regimen to women who refuse to undergo standard radiotherapy. We report our outcomes and a cost analysis. Between 2000 and 2012, 84 patients participated in this IRB-approved study and underwent whole breast radiation to 23 Gy in four fractions. Local control and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
1
7
0
2
Order By: Relevance
“…Hypofractionation in breast cancer is seen to provide promising local control rates and good cosmetic outcomes . Published data from the UK START trials confirm the safety and efficacy of hypofractionated breast radiation therapy, negating prior concerns of long‐term (cardiac) post‐treatment management .…”
Section: Discussionmentioning
confidence: 97%
“…Hypofractionation in breast cancer is seen to provide promising local control rates and good cosmetic outcomes . Published data from the UK START trials confirm the safety and efficacy of hypofractionated breast radiation therapy, negating prior concerns of long‐term (cardiac) post‐treatment management .…”
Section: Discussionmentioning
confidence: 97%
“…Économiquement, l'hypofractionnement est clairement rentable pour le système de santé, comme cela a déjà été démontré [20]. Il est important de noter que l'oncologue radiothérapeute est le prescripteur du nombre des séances, ainsi que par corolaire des transports et que selon l'article L. 162-2-1 du Code de la sécurité sociale le prescripteur est tenu d'observer la « plus stricte économie compatible avec la qualité, la sécurité et l'efficacité des soins ».…”
Section: Discussionunclassified
“…Notre étude a aussi montré que 20 % des patientes pourraient être candidates pour un hypofractionnement. Une comparaison des coûts avec ceux estimés par Min et al montre que notre système de santé est proche du système américain [20]. Ils ont effectivement estimé une réduction de 221 $ (environ 175 D ) par séance, (sans coût de transport) contre 170,77 D .…”
Section: Discussionunclassified
“…Therefore, longer courses of radiation and the use more advanced technology such as IMRT further increases payments relative to simpler or shorter techniques of radiation delivery [5,26,27]. Multiple randomized trials in breast cancer have demonstrated no clinical difference between shorter courses (hypofractionated) and longer courses of radiation in terms of toxicity or tumor control[28,29].…”
Section: Discussionmentioning
confidence: 99%